How Do You Feel? Subjective Perception of Recovery as a Reliable Surrogate of Cognitive and Functional Outcome in Cardiac Arrest Survivors. Issue 4 (April 2018) - Juan, Elsa; De Lucia, Marzia; Beaud, Valérie; Oddo, Mauro; Rusca, Marco; Viceic, Dragana; Clarke, Stephanie; Rossetti, Andrea O.
Abstract : Objectives: To show that subjective estimate of patient's condition is related to objective cognitive and functional outcome in cardiac arrest survivors. Design: Longitudinal cohort study. Setting: ICU and Neuropsychology Service in two hospitals in Switzerland. Patients: Fifty survivors included from a prospective cohort of 138 patients admitted at the ICU for cardiopulmonary arrest. Interventions: Comprehensive cognitive and functional evaluation at 6 months follow-up. Measurements and Main Results: Subjectively, 70% of survivors reported satisfactory recovery and 29% reported no complaints. Objectively, 76% were classified as good neurologic outcome (Cerebral Performance Category 1), 26% as having no symptoms (modified Rankin Scale 0), and 38% as upper good recovery (Glasgow Outcome Scale Extended 1). Cognitive assessment detected substantial cognitive impairment in 26%, primarily concerning processing speed, language, long-term memory, and executive functions. Subjective complaints severity correlated significantly with objective cognitive impairment ( r S = 0.64; p < 0.001). Finally, patients reporting unsatisfactory recovery displayed lower functional scores than those reporting satisfactory recovery (e.g., quality of life satisfaction: 64% vs 81%; Z = 2.18; p = 0.03) and more cognitive impairment (three vs one cognitive domains impaired; Z = –3.21; p < 0.001), concerning in particular learning and long-term verbal and visual memory. Conclusions: Long-term subjective and objective outcome appears good in the majority of cardiac arrest survivors. Specific functional and cognitive impairments were found in patients reporting unsatisfactory recovery. Subjective recovery was strongly correlated with objective assessment. Abstract : Supplemental Digital Content is available in the text.